The Role of Civil Commitment in the Opioid Crisis. Issue 2 (June 2018) - Bhalla, Ish P.; Cohen, Nina; Haupt, Claudia E.; Stith, Kate; Zhong, Rocksheng
This article seeks to shed light on civil commitment in the context of the opioid crisis, to sketch the existing legal landscape surrounding civil commitment, and to illustrate the relevant medical, ethical, and legal concerns that policymakers must take into account as they struggle to find appropriate responses to the crisis.